(untitled) (Journal of Politics and International Studies, 2023)
Social media has brought revolution in the world of politics as well. It has affected the ways by which public get knowledge, build opinions and influence political syste. This study aims to highlight this deep impact of social media on public opinion in the context of General Election of 2018 in Pakistan. The research analyzes the Facebook and Twitter to observe its influence over voter’s opinions, political system and the results of General Elections 2018. The two biggest parties of Pakistan i.e. Pakistan Tehreek e Insaaf (PTI) and Pakistan Muslim League Nawaz (PML-N) used social media to increase their share of vote as well as to get support of their voters on a mass level. The research attempts to shed insight on how political parties employ tactics for the digital world participation, dissemination of information, and public participation throughout their election campaigns. "Social Learning Theory" serves as the overarching framework for this research. Descriptive analytic approaches are employed to des cribe and summarize the findings of this qualitative study. An analytical method is applied to assess the data critically. The study reveals that during general elections 2018s, Facebook and Twitter helped political parties with their electoral campaigns and mass mobilization. PTI's dynamic strategy and efficient communication were crucial in gaining victory against PML-N.